Development of a One-Step Multiplex Real-Time PCR Assay for the Detection of Viral Pathogens Associated With the Bovine Respiratory Disease Complex - Zhang, Juan; Wang, Wan; Yang, Mujiao; Lin, Jun; Xue, Fei; Zhu, Yuanmao; Yin, Xin (Frontiers in Veterinary Science, 2022)
Bovine respiratory disease complex (BRDC) occurs widely in cattle farms. The main viral pathogens include bovine viral diarrhea virus (BVDV), Bovine herpesvirus 1 (BoHV-1), bovine parainfluenza virus type 3 (BPIV3), and bovine respiratory syncytial virus (BRSV), and the newly emerged influenza D virus (IDV). In this study, we have developed a one-step multiplex real-time Polymerase Chain Reaction (PCR) capable of simultaneously detecting these five viral pathogens causing BRDC. The established assay could specifically detect targeted viruses without cross-reaction with others. The detection limit was 10 copies/reaction for single real-time PCR and 100 copies/ reaction for multiplex real-time PCR assay. A total of 213 nasal samples from cattle with signs of respiratory tract disease were then collected for performance evaluation of the established platform, proving that the method has good specificity and sensitivity. The surveillance data suggested that BVDV and BoHV-1 infections are the dominant cause of BRDC in the herd, whereas the detection rate of IDV, BIPV3, and BRSV is relatively lower. In summary, the established assay provides technical support for rapid clinical detection of BRDC associated viral pathogens to guide the formulation of BRDC prevention and control measures.